The structure of a franchise disclosure document for a new franchise system in Malaysia - Mohd Harif, Mohd Amy Azhar; Perry, Chad; McCosker, Colin F; Mahad Noor, Norsyema Hani (2001)
Franchising is the fastest growing method of doing business.In Malaysia in particular, franchising has been aggressively promoted by the government since the early 1990s.However, there is little academic research to guide or regulate industry practices.Thus this research investigates the process of developing a new franchise system, with particular reference to the elements of franchise disclosure documents.This research used action research methodology to develop a new practical framework of franchise disclosure documents within the Malaysian government department that handles franchise regulation. Three main action research cycles (with two mini-action cycles for each main cycle) were conducted with three new franchise systems seeking to register with the Registrar of Franchise.To triangulate the findings of the action research, the researcher also presented them at a National Franchise Workshop.These activities showed that the franchise disclosure documents should comprise 25 elements: 9 elements of financial planning and 16 elements of non-financial items. This practical framework for franchise disclosure documents in a new franchise system was adopted by the Registrar of Franchise in Malaysia.